Drugs for the Quorum Sensing Inhibition of Oral Biofilm: New Frontiers and Insights in the Treatment of Periodontitis - Alessandro Polizzi; Martina Donzella; Giada Nicolosi; Simona Santonocito; Paolo Pesce; Gaetano Isola (MDPI AG, 2022)
Chemical molecules are used by microorganisms to communicate with each other. Quorum sensing is the mechanism through which microorganisms regulate their population density and activity with chemical signaling. The inhibition of quorum sensing, called quorum quenching, may disrupt oral biofilm formation, which is the main etiological factor of oral diseases, including periodontitis. Periodontitis is a chronic inflammatory disorder of infectious etiology involving the hard and soft periodontal tissues and which is related to various systemic disorders, including cardiovascular diseases, diabetes and obesity. The employment of adjuvant therapies to traditional scaling and root planing is currently being studied to further reduce the impact of periodontitis. In this sense, using antibiotics and antiseptics involves non-negligible risks, such as antibiotic resistance phenomena and hinders the re-establishment of eubiosis. Different quorum sensing signal molecules have been identified in periodontal pathogenic oral bacteria. In this regard, quorum sensing inhibitors are emerging as some interesting solutions for the management of periodontitis. Therefore, the aim of this review is to summarize the current state of knowledge on the mechanisms of quorum sensing signal molecules produced by oral biofilm and to analyze the potential of quorum sensing inhibitors for the management of periodontitis.